Higher Order Nonlinear Effect and Limitation of Soliton Propagation in Dispersive-Nonlinear Medium for Dispersion-Shifted Fiber - Mohammed, Abbou Fouad; Chuah, Hean Teik; Majumder, Satya Prasad (Ingenta, 2001)
A computer simulation of the nonlinear Schrodinger equation is carried out to evaluate the impact of nonlinear susceptibility of a single mode fiber on the transmission of a soliton pulse. The third and fifth order nonlinear susceptibilities are considered in the simulation. The results show that the output soliton pulse shape strongly depends on the third order nonlinear susceptibility and gets distorted when the full width half maximum (FWHM) pulse width is of the order of 10ps or less.